2013
DOI: 10.1002/2013jb010388
|View full text |Cite
|
Sign up to set email alerts
|

Seismic attenuation beneath northeastern Japan: Constraints on mantle dynamics and arc magmatism

Abstract: [1] We apply a three-step approach to estimate three-dimensional (3-D) P wave attenuation (Q p À1 ) structure beneath northeastern Japan. First, corner frequencies of earthquakes are determined using the spectral-ratio method for S-coda waves. Then, whole-path attenuation terms, t*, and site-amplification factors are simultaneously estimated by a joint inversion. The set of t* is finally inverted for 3-D attenuation structure. The results show that the mantle wedge has low attenuation in the fore arc and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 68 publications
8
114
0
Order By: Relevance
“…This region is slightly above and parallel to the slab surface at the 60-120 km depth range (Kawakatsu and Watada, 2007;Nakajima et al, 2013;Tsuji et al, 2008), as shown by the "V s jump zone" in Fig. 11A.…”
Section: Implications For Water In the Mantle Wedgementioning
confidence: 86%
See 1 more Smart Citation
“…This region is slightly above and parallel to the slab surface at the 60-120 km depth range (Kawakatsu and Watada, 2007;Nakajima et al, 2013;Tsuji et al, 2008), as shown by the "V s jump zone" in Fig. 11A.…”
Section: Implications For Water In the Mantle Wedgementioning
confidence: 86%
“…Seismic tomography (Hasegawa et al, 1991;Nakajima and Hasegawa, 2003;Nakajima et al, 2005;Tsuji et al, 2008;Zhao et al, 1992) and receiver function (Kawakatsu and Watada, 2007) studies for this arc have led to its relatively well-understood substructure. The deep slab and mantle seismicity is related to slab dehydration; the migration of water through the slab and mantle has also been investigated Nakajima et al, 2013;Shiina et al, 2013). The correlations of these geophysical observations and petrological and geochemical processes were examined in terms of the ABS4 model perspective .…”
Section: Cold Subduction Zone: Ne Japanmentioning
confidence: 99%
“…We used α = 0.27 because α = 0.2-0.3 has been estimated for the crust and the uppermost mantle beneath the Japanese Islands Nakajima 2014;Saita et al 2015) and this value range is the most appropriate value for the mantle (e.g., Jackson et al 2002). We constructed a set of observation equations for multiple earthquakes at a single station and carried out a simultaneous inversion for t * 0 and relative site amplification factors (for details, see Nakajima et al 2013). As values of f c estimated by the coda spectral ratio technique were for S waves, we calculated values of f c for P waves by assuming the relationship f cp = 1.33 × f cs (Uchida et al 2007).…”
Section: Attenuation Term and Site Amplification Factormentioning
confidence: 99%
“…Here we estimate the 3D P-wave attenuation (Q p −1 ) structure in central Japan using waveform data recorded by a dense nationwide seismic network. We use a threestep approach developed by Nakajima et al (2013) to delineate the 3D Q p −1 structure, which can minimize the potential trade-offs among unknown parameters. The corner frequency (f c ) of each earthquake is first estimated by the S-coda spectral ratio method.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous fluids and volatiles released by dehydration of hydrous minerals contribute to the genesis of intraslab earthquakes (e.g., Kirby et al 1996) and arc magmatism (e.g., Nakajima et al 2013).…”
Section: Introductionmentioning
confidence: 99%